Answer:
Slower speed = 9 mph
Step-by-step explanation:
Let the initial speed (slower speed) = s mph
Speed 's' = ![\frac{\text{Distance}}{\text{Time}}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Ctext%7BDistance%7D%7D%7B%5Ctext%7BTime%7D%7D)
s =
-------(1)
If the cyclist increases the speed by 3 mph then the final speed = (s + 3) mph
He can reduce the time 't' by 10 minutes (
hours)
Now, (s + 3) = ![\frac{6}{t-\frac{1}{6}}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7Bt-%5Cfrac%7B1%7D%7B6%7D%7D)
s + 3 =
--------(2)
Substitute the value of 's' from equation (1) to the equation (2).
![\frac{6}{t}+3=\frac{36}{6t-1}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7Bt%7D%2B3%3D%5Cfrac%7B36%7D%7B6t-1%7D)
![\frac{2}{t}+1=\frac{12}{6t-1}](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7Bt%7D%2B1%3D%5Cfrac%7B12%7D%7B6t-1%7D)
![\frac{2}{t}-\frac{12}{6t-1}=-1](https://tex.z-dn.net/?f=%5Cfrac%7B2%7D%7Bt%7D-%5Cfrac%7B12%7D%7B6t-1%7D%3D-1)
![\frac{2(6t-1)-12t}{t(6t-1)}=-1](https://tex.z-dn.net/?f=%5Cfrac%7B2%286t-1%29-12t%7D%7Bt%286t-1%29%7D%3D-1)
![\frac{12t-2-12t}{t(6t-1)}=-1](https://tex.z-dn.net/?f=%5Cfrac%7B12t-2-12t%7D%7Bt%286t-1%29%7D%3D-1)
![-\frac{2}{t(6t-1)}=-1](https://tex.z-dn.net/?f=-%5Cfrac%7B2%7D%7Bt%286t-1%29%7D%3D-1)
6t² - t = 2
6t² - t - 2 = 0
6t² - 4t + 3t - 2 = 0
2t(3t - 2) + 1(3t - 2) = 0
(2t + 1)(3t - 2) = 0
t =
hours
But the time can't be negative.
Therefore, t =
hours is the answer.
From equation (1),
s = ![\frac{6}{\frac{2}{3}}](https://tex.z-dn.net/?f=%5Cfrac%7B6%7D%7B%5Cfrac%7B2%7D%7B3%7D%7D)
s = 9 miles per hour.
Slower speed = 9 mph is the answer.